" Petrophysical evaluation and depositional environments of reservoir sands of x field, offshore Niger delta, Nigeria " (2009)
" This study involves the use of geophysical well logs to characterize four reservoir sand bodies contained in four wells offshore Western Niger Delta. The well logs include caliper, SP, gamma ray, resistivity, neutron (NPHI), density (RHOB) and sonic logs. The logs were obtained in digital data format and a Paradigm's petrophysical software, Geolog was used to process the data into log images. This aided the visual identification of lithologies and potential reservoirs. The reservoirs are contained in the Agbada Formation of the Niger Delta and are composed of sandstone and unconsolidated sands. The sands are predominantly medium to coarse grained with shale intercalations in some horizons. Thickness ranges between 33-60ft (10 to 18 metres). The reservoir characteristics are controlled by depositional environment and depth of burial. From gamma ray log motifs, the reservoirs are inferred to be deep sea turbidite fans and tidal ridge sands. Porosity and permeability values are high with average values of 25% and 4500 millidarcies respectively. Shale content is generally low across the reservoir sands with average values of 15%. The sands are characterized by high relative permeability to oil, Km Km is as high as 1.0 in some horizons. This suggests that oil can be produced relative to water. Generally, porosity and permeability are known to decrease with depth of burial in the Niger Delta. However, a situation of increased porosity and permeability with depth of burial was observed in one of the reservoirs. This can attributed to the preservation of secondary porosity in a mechanically stable, compaction resistant framework of quartz grains. . " "